PENERAPAN NILAI-NILAI KEAGAMAAN DALAM MENGATASI KEDISIPLINAN SISWA DI MADRASAH ALIYAH INTEGRATIF NAHDLATUL ULAMA AL-HIKMAH JERU TUMPANG - Nurul Lailatul Ahmaliya; Ali Rif’an Rif’an (Journal Islamic Studies, 2023)
The application of religious values is an act carried out by a person to practice a theory that has become a shari'a decree that has a relationship between man and his god, and is applied in his daily life. Besides religious values, discipline is also very important to be applied in everyday life. This study uses a qualitative approach and the type of case study research which takes place at the Integrative Madrasah Aliyah NU Al-Hikmah Jeru Tumpang, and uses interview, observation, and documentation techniques. Religious values developed at Madrasah Aliyah Integrative NU Al-Hikmah Jeru Tumpang are Religious Values, Moral Values, Love for Peace, Honesty Values, Love to Read. in the process of applying religious values to overcome student discipline includes planning, implementation, and evaluation processes. the challenges in this case are disciplinary regulations, istighotsah activities that are less than optimal and student discipline towards the completeness of attributes.